2013
DOI: 10.3390/md11124773
|View full text |Cite
|
Sign up to set email alerts
|

A New in Vitro Anti-Tumor Polypeptide Isolated from Arca inflata

Abstract: A new in vitro anti-tumor polypeptide, coded as J2-C3, was isolated from Arca inflata Reeve and purified by diethyl-aminoethanol (DEAE)-sepharose Fast Flow anion exchange and phenyl sepharose CL-4B hydrophobic chromatography. J2-C3 was identified to be a homogeneous compound by native polyacrylamide gel electrophoresis (Native-PAGE). The purity of J2-C3 was over 99% in reversed phase-high performance liquid chromatography (RP-HPLC). The molecular weight was determined as 20,538.0 Da by electrospray-ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The absorption at 1398 cm −1 should be assigned to the stretching vibration of C-N in the amide. The peaks at 1200~1000 cm −1 suggested the presence of ring vibrations overlapped with stretching vibrations of C-OH and C-O-C. [36] Based on this analysis of the FTIR spectra, there were no significant differences between any of the fractions in terms of secondary structure.…”
Section: Validation Of the Modelmentioning
confidence: 70%
“…The absorption at 1398 cm −1 should be assigned to the stretching vibration of C-N in the amide. The peaks at 1200~1000 cm −1 suggested the presence of ring vibrations overlapped with stretching vibrations of C-OH and C-O-C. [36] Based on this analysis of the FTIR spectra, there were no significant differences between any of the fractions in terms of secondary structure.…”
Section: Validation Of the Modelmentioning
confidence: 70%
“…P2 found to have anticancer activity on cervical cancer (HeLa) and colon (HT 29) cancer on the other hand H3 has proved to have antioxidant activity along with antiproliferative activity on colon (HT 29) and hepatocarcinoma (HepG2) cancer 22 . Another polypeptide J2-C3 isolated from clam Arca inflata reported to show antitumor effect on lung (A549) cancer, colon cancer (HT 29) and hepatic carcinoma (Hep G2) 23 . Peptide (MW-3147 Da) from Meretrix meretrix showed anticancer activity upon BGC-823 24 .…”
Section: Discussionmentioning
confidence: 99%
“…We performed MTT cell viability experiments and determined that the recombinant J2-C2 did not significantly affect cell viability and proliferation of MCF7, PC3 and HT29 ( Figure 2). In studies conducted by Jian Xu et al (2013), it was reported that native J2-C2 isolated and purified from Arca inflata showed antiproliferative effect against A549, SPC-A-1 and HepG2 cell lines (Zhu et. al., 2017).…”
Section: Mtt Cell Viability Assaymentioning
confidence: 99%